2019
DOI: 10.1039/c8dt04699a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient metal(iii) porphyrin and salen complexes for the polymerization of rac-lactide under ambient conditions

Abstract: Metal(iii) complexes supported by porphyrin and salen ligands were highly efficient for rac-lactide polymerization at room temperature giving isotactic-enriched PLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 63 publications
1
29
1
Order By: Relevance
“…12 We recently reported the first series of aluminium catam complexes which was found able to catalyse rac-lactide ROP at room temperature; 13 a rather rare feature for aluminium-based catalysts. [14][15][16][17] Here, we report the benefit of hydrogen bond donors in the catalytic pocket to explain the high activity and stereoselectivity of a new family of aluminium catam complexes in rac-lactide ROP. Structural characterization of the catalysts, mechanistic, kinetic (including isotope effect) and computational studies highlight the benefit of such noncovalent interactions.…”
Section: Toc Graphicmentioning
confidence: 97%
See 1 more Smart Citation
“…12 We recently reported the first series of aluminium catam complexes which was found able to catalyse rac-lactide ROP at room temperature; 13 a rather rare feature for aluminium-based catalysts. [14][15][16][17] Here, we report the benefit of hydrogen bond donors in the catalytic pocket to explain the high activity and stereoselectivity of a new family of aluminium catam complexes in rac-lactide ROP. Structural characterization of the catalysts, mechanistic, kinetic (including isotope effect) and computational studies highlight the benefit of such noncovalent interactions.…”
Section: Toc Graphicmentioning
confidence: 97%
“…: i) an heterobimetallic aluminium-lithium complex featuring an anionic aluminium supported by a NON-type diamido ether tridentate ligand, and ii) in-situ generated anionic aluminium complexes bearing salen-or porphyrinato-type ligands in the presence of epoxide (CHO, PO) and ammonium halide salt. [14][15][16][17] However, 2 is the first example of a well-defined discrete monometallic aluminium catalyst exhibiting both significant heteroselectivity and activity at room temperature (< 30 °C) for rac-lactide. In comparison, the analogous aluminium salen and H salan complexes featuring the same propyl backbone displayed lower activities at higher temperatures (>70 °C) than catalyst 1 and 2 at room temperature (Table 1, entry 6-7 and Figure S10).…”
Section: Toc Graphicmentioning
confidence: 99%
“…A range of metal complexes and ligand frameworks have been studied as single-site initiators 6,13,[14][15][16][17] for the stereoselective ROP of lactide (indium, [18][19][20][21] scandium and yttrium, [22][23][24][25][26][27] lanthanum 28,29 samarium, 29 and iron 30 ). For the polymerisation of rac-lactide, high levels of isotactic stereocontrol were observed when using indium initiators (P m up to 0.87), while highly heterotactic PLA was obtained for yttrium initiators (P r > 0.87).…”
Section: Introductionmentioning
confidence: 99%
“…Quaternary ammonium salts have been reported to enhance the catalytic activity of a variety of homogeneous Al-Cl catalysts [10,13,39] including 5b. [9] However, addition of PPNCl (2 equivalents) to complex 2b unexpectedly resulted in a 15-fold drop in reactivity (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies by Thomas, Maron et al revealed that salen-AlCl catalysts, which are generally poor initiators for ROP, [8] could achieve high catalyst activities when combined with an epoxide and an onium salt co-catalyst to generate an Al-alkoxide in situ (Figure 1). [9] This method of initiating ROP and ring-opening copolymerisations has gathered attention, [10][11][12] and epoxides have been utilised as in situ activators for rac-LA ROP with porphyrin-AlCl, [13] Sn(octanoate)2, [14] and salen-FeCl systems. [15][16][17] The homogeneous Al-Cl catalysts generally require the presence of a cocatalyst such as PPNCl for efficient ROP initiation.…”
Section: Introductionmentioning
confidence: 99%